2014
DOI: 10.1007/s13304-014-0275-y
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative neuromonitoring in thyroid surgery: a point prevalence survey on utilization, management, and documentation in Italy

Abstract: The frequency of neuromonitoring during thyroid surgery is underreported in Italy. The present survey depicts and describes the patterns of use, management, documentation for IONM devices of IONM during thyroid surgery by surgeons in Italy. A point prevalence survey was undertaken. Source data were mixed from Italian surgeons attending the 2014 International Neuromonitoring Study Group (INMSG) meeting, four IONM manufacturers available in Italy and surgical units were identified from Company sales data. Qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Dionigi et al recently published outcomes of a point prevalence survey on utilization, management, and documentation of intraoperative neuromonitoring in thyroid surgery in Italy . Source data were mixed from Italian surgeons attending the Annual Meeting of the INMSG in 2014, four IONM manufacturers available in Italy, and surgical units identified from company sales data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dionigi et al recently published outcomes of a point prevalence survey on utilization, management, and documentation of intraoperative neuromonitoring in thyroid surgery in Italy . Source data were mixed from Italian surgeons attending the Annual Meeting of the INMSG in 2014, four IONM manufacturers available in Italy, and surgical units identified from company sales data.…”
Section: Discussionmentioning
confidence: 99%
“…The survey revealed that participants had limited experience with the standardized approach for IONM (28%). General IONM information to patients and/or subsequent specific IONM informed consent was initiated in 8% of centers …”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative neural monitoring (IONM) for thyroid and parathyroid surgery is one of several important technological advancements incorporated into head and neck surgery . IONM has become increasingly prevalent, with many surgeons using it routinely . Although IONM has become more widespread, universal incorporation and attitudes toward its utility in preventing recurrent laryngeal nerve (RLN) dysfunction have remained heterogeneous …”
Section: Introductionmentioning
confidence: 99%
“…This allows evoked surface electromyography (EMG) monitoring of the left and right thyroarytenoid muscles during stimulation of recurrent laryngeal nerve (RLN) and vagus nerve (VN) . Endotracheal tube‐based surface recording electrodes systems are now commonly applied because of their availability and significant advantages over needle electrodes inserted into thyroarytenoid muscle (noninvasive nature, safety, ease of setup, and use) . Novel EMG tubes have been developed to achieve optimal RLN and external branch of the superior laryngeal nerve monitoring …”
Section: Introductionmentioning
confidence: 99%